Body check - Kennedy, Elle (Harlequin Enterprises ULC, 2024)
"After a childhood spent being dragged around the country by her hockey coach father, Hayden Houston intends to take some time to figure out her future. Whether that future will include her currently off-again boyfriend remains to be seen. What it certainly won't include is the for-one-night-only guy she just met at a bar. It seems hockey star Brody Croft did not get the memo about being temporary. Big, bold and driven, he's dedicated in everything he does. Up till now, that's been his team--the one owned by Hayden's dad. But his night with Hayden has sparked something he didn't expect. The two of them are good together. Really good. There's a connection he's never experienced before, one he knows they'd be wrong to ignore. Even with a game-fixing scandal testing both their loyalties--to teammates, to friends...to family. Part of Hayden wants to turn tail and run. A complicated relationship with a bad boy hockey player is exactly what she never wanted. But when it comes to Brody, Hayden is realizing that people can be so much more than what they seem"--